The role of big 5 personality traits in determining ethical behaviour for hospitality industry employees in Malaysia / Nur Lelawati Jamaludin, Patrick Mehon - Jamaludin, Nur Lelawati; Mehon, Patrick (Universiti Teknologi MARA Cawangan Sarawak, 2020)
This study begins from the realisation of the important contributions of employees’ personality traits and ethical behaviour in the workplace to business success. Therefore, it is imperative that further studies are conducted especially in Hospitality Industry in Malaysia, where there is paucity of research in this area. This study aims to understand the relationship of the Big Five personality traits (Extraversion, Openness to Experience, Conscientiousness, Agreeableness, and Neuroticism) in predicting ethical behaviour of employees. A sample of 150 employees from The Ritz-Carlton Hotel Kuala Lumpur accepted the invitation and filled out the survey questionnaire. In a series of regression analyses, we found that the studied variables accounted for 92.8% of the variance in employees’ ethical behaviour. Results show that for the employees at The Ritz-Carlton Hotel Kuala Lumpur, Openness to Experience personality trait contributes the most to ethical behaviour at their workplace, followed by Agreeableness and Conscientiousness. This paper discusses the results from the social, psychological, and human resource perspectives, as well as their implications for human resource management